Invasive Solid Mucinous Papillary Carcinoma Breast with Neuroendocrine Differentiation: A Case Report with Immunohistochemical Study - Mishra, Jyoti; Srivastav, Srijan; Singh, Natasha; Prasad, Varun (Annals of Pathology and Laboratory Medicine, 2020)
Solid papillary carcinoma of the breast (SPCB) is a distinctive form of papillary carcinoma that tends to occur in older women and usually has a favorable prognosis. We describe an invasive solid papillary carcinoma with extracellular and intracellular mucin and neuroendocrine differentiation in a 60-year old female. The cytological features have been also been highlighted with an insight on differentials that were helpful in its correct identification preoperatively.